Enhanced Photoelectrochemical Performance of Zn-Doped Bi2s3 Thin Films Via Seed-Layer-Assisted Growth - Radhalayam, D (ROYAL SOC CHEMISTRY, 2025)
Bismuth sulfide (Bi2S3) is a promising material for photoelectrochemical (PEC) water splitting, but its performance is limited by poor charge transport and high electron-hole recombination. This study enhances Bi2S3 performance by doping it with Zn using a seed-layer (SL) approach during chemical bath deposition. Three film types were prepared on FTO glass: pristine Bi2S3, SL-grown Bi2S3, and Zn-doped Bi2S3 (0.74-1.1 at%). The SL method improved the crystallinity and nanorod morphology, and reduced the bandgap from 1.4 to 1.32 eV. Zn doping induced a morphological shift to nanoparticles, increased the bandgap to 1.45 eV, and resulted in smaller crystallites. PEC analysis showed photocurrent densities of 4.5 mA cm-2 (pristine), 10 mA cm-2 (SL-grown), and 12.3 mA cm-2 (Zn-doped) at 1 V vs. Ag/AgCl. The Zn-doped films exhibited improved stability and resistance to photocorrosion. The synergistic effects of SL growth and Zn doping significantly enhanced the structural, optical, and PEC performance of Bi2S3, making Zn-doped Bi2S3 a strong candidate for solar-driven water splitting.